PEMERATAAN PENDIDIKAN DI DAERAH TERPENCIL INDONESIA DALAM PERSPEKTIF HAKIKAT BELAJAR KI HAJAR DEWANTARA - Putrisalima, Aida; M. Mamduh Winangun (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
Educational inequality in remote areas still occurs a lot, especially in 3T (Disadvantaged, Frontier, and Outermost) areas until now it is still a quite serious problem. With geographical conditions that are very difficult to reach, limited educators, and lack of educational facilities that make access to learning for children in the area uneven. With the essence of learning theory from Ki Hajar Dewantara who strongly views that the learning process should provide space for the development of children's creation, taste, and karsa freely, not just the other way around. On the other hand, it can be seen by the among method and the cooperation of the three educational centers, families, schools, and communities in rural environments. This research uses secondary data based on official reports, news, and journal articles according to problems that often arise. At the end of the analysis, it shows that there are still a lot of obstacles in terms of education in remote areas because the learning environment is not supportive for the optimal development of students' potential. Based on the conditions that occur, the application of the among approach by teachers, the role of the community itself, and the development of a curriculum that is better than before are important steps to encourage the creation of a more inclusive and equitable education.